Geographical features of the structure and production of technical crops by altitude zones in the north-western part of Azerbaijan on the example of the Ganja-Dashkasan and Gazakh-Tovuz economic regions - Abbasova, Aida A. (Journal of the Belarusian State University. Geography and Geology, 2025)
The north-western part of Azerbaijan is recognised as an important center for the cultivation of technical crops such as sunflower, cotton and sugar beet. In this region, over the past decade, the area allocated for the cultivation of technical crops has more than doubled, and the production of these crops has increased six fold. Using the example of the Ganja-Dashkasan and Gazakh-Tovuz economic regions, the structure of technical crops and their distribution by altitude zones in the north-western part of Azerbaijan are considered. The study was conducted using regional statistical data and the results of the analysis carried out during the survey of this part of the country. By applying this combined approach, it was possible to determine the characteristics of growing technical crops at different altitudes and estimate the yield of these crops. It is emphasised that good natural conditions are not enough for the cultivation of technical crops and it is necessary to use agrotechnical methods and innovative approaches to growing plants taking into account the characteristics of the crop.
Keywords: economic region; agricultural specialisation; altitude zones; structure of technical crop production; Azerbaijan